Lavado broncoalveolar y derrame pleural con hipereosinofilia. Caso clínico y revisión de la literatura - Fernández-Bussy, Sebastián; Campos, Felipe; Ogueta, Isabel; Labarca, Gonzalo; Cabello, Hernán (Revista Médica de Chile, 2016)
Chronic eosinophilic pneumonia (CEP) is uncommon and predominantly seen in women. More than 6% of eosinophils in peripheral blood and more than 25% in bronchoalveolar lavage are diagnostic criteria. Secondary causes of hypereosinophilic pneumonia must be ruled out. We report a 72 years old non-smoker man presenting in the emergency room with a history of cough, fever, and moderate dyspnea. He was not taking any medication. A chest-X ray showed a left lower lobe (LLL) consolidation, and was started on broad-spectrum antibiotics with a presumptive diagnosis of pneumonia. There was no improvement after therapy. A chest CT scan showed increased LLL consolidation and new left upper lobe ground glass opacities as well as a moderate left pleural effusion. Flexible bronchoscopy was performed and bronchoalveolar lavage showed 95% eosinophils, and had negative cultures. No parasites were identified. Transbronchial biopsies demonstrated eosinophil accumulation in alveoli and interstitium and pleural fluid was composed by 85% eosinophils. With the diagnosis of CEP, systemic corticosteroids were used with favorable clinical and radiological response.